2021
DOI: 10.1108/ccij-03-2021-0035
|View full text |Cite
|
Sign up to set email alerts
|

Framing sports' corporate social responsibility: US women's vs men's soccer leagues

Abstract: PurposeThis investigation's purpose is to compare coverage of the corporate social responsibility (CSR) behaviors of the National Women's Soccer League (NWSL) and Major League Soccer (MLS). The goals are (1) to extend CSR analyses beyond organizational reports and (2) to compare coverage of professional sports teams' CSR behaviors across genders.Design/methodology/approachSpecifically, this quantitative content analysis compared local newspaper coverage of the socially responsible behaviors of the three NWSL a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…we can learn from the mistakes that you've made in the past and create something completely different" (CC). This debate is often raised in the media, but is not covered in academic literature beyond general representation of women in the football industry (Bryan et al, 2021) and commercial considerations linked to social responsibility (Painter et al, 2021). Research around governance in women's football is lacking and thus the research gap here is large.…”
Section: Football Reformsmentioning
confidence: 99%
See 1 more Smart Citation
“…we can learn from the mistakes that you've made in the past and create something completely different" (CC). This debate is often raised in the media, but is not covered in academic literature beyond general representation of women in the football industry (Bryan et al, 2021) and commercial considerations linked to social responsibility (Painter et al, 2021). Research around governance in women's football is lacking and thus the research gap here is large.…”
Section: Football Reformsmentioning
confidence: 99%
“…This debate is often raised in the media, but is not covered in academic literature beyond general representation of women in the football industry (Bryan et al. , 2021) and commercial considerations linked to social responsibility (Painter et al. , 2021).…”
Section: Football Reformsmentioning
confidence: 99%
“…Firstly, Dahlsrud (2006) conducted a factor analysis on CSR approaches and concluded that CSR included voluntarily addressing specific functions, ethics, and regulatory frameworks that are pertinent to the development of business sustainability and behavior that society expects the business to demonstrate. Secondly, in order for businesses to rationalize CSR, it must include capacity to reduce cost and risk, build a reputation in the market, create a competitive advantage, act in a socially responsible manner, and build synergy across stakeholder groups through the creation of social capital (Hwang & Chung, 2020; Jamali & Karam, 2018; Kurucz et al, 2008; Painter et al, 2022; Raimo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the past three years, CCIJ has increased the publication of EDI/DEI topics by publishing works in a wider area of equality such as gender quotas (Lefley and Janecek, 2023, Hamplová et al , 2022), female journalists and their leadership experiences (Cunha and Lúcio Martins, 2023), female empowerment and internal communication (Li et al ., 2023), gender and the office culture (Polić and Holy, 2021; Tripathi et al ., 2023), femvertising (Lima and Casais, 2021), gender and leadership (Zeler et al ., 2022; Zheng et al ., 2023, Meng and Neill, 2023), CSA and gender equality (Marschlich and Bernet, 2024), JEDI issues and media irresponsibility (Painter and Sahm, 2023), CSR and gender (Painter et al ., 2022), and these are just articles published during my editorship and excluding some special issue articles. Therefore, CCIJ is emerging as a journal that increasingly publishes equality scholarship in corporate communication, contributing towards knowledge creation in this field as well as widening participation and bringing inclusivity to scholarship by opening doors to equality scholars in corporate communication.…”
mentioning
confidence: 99%